POLYFUNCTIONALITY IN FORMS OF FUTURE TENSE OF UZBEK AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2024)
In the process of learning a certain foreign language, the topic of verb tenses in this language is considered one of the most widely covered parts. Because it is very important to use the appropriate form of the verb to show the events that happened at different times in the correct expression of an idea. In this case, the grammatical category of tense in the languages of the world is interpreted as a set of grammatical forms used to indicate the time of the action expressed by the verb. Although it is believed that there are present, past and future forms of verbs in Uzbek and English, not all researchers support this opinion. This, of course, is caused by the nature of syncretic characteristic of these forms, the polyfunctional manifestation of these features in speech. In this article, the opinions of various researchers who have studied the field of verbs in the contrasted languages are considered, and the authorʼs attitude towards them is expressed, and the presence of future tense forms in Uzbek and English languages is proved. Polyfunctional aspects of syncretic tenses are explained by comparing examples from the two languages. On the basis of conducted research and analysis of examples, it is concluded that future tense forms in the compared languages realize their syncretic nature and show their polyfunctional characteristics.